Beta-amyloid activates NLRP3 inflammasome via TLR4 in mouse microglia. (25th September 2020) - Liu, Yang; Dai, Yue; Li, Qing; Chen, Chen; Chen, Hao; Song, Yuanjian; Hua, Fang; Zhang, Zuohui
Highlights: Aβ1−42 -induced NLRP3 inflammasome activation in BV-2 microglia is mediated through TLR4. TLR4/NLRP3 signaling plays a critical role in Aβ1−42 -induced inflammation. Inhibition of TLR4/NLRP3 signaling attenuates Aβ1−42 -induced inflammation and contributes to neuroprotection. Abstract: Beta-amyloid(Aβ)-induced inflammation plays a critical role in the pathogenesis of Alzheimer's disease (AD). Nod-like receptor nucleotide-binding domain leucine rich repeat containing protein 3 (NLRP3) inflammasome is involved in the Aβ-induced inflammation. However, the mechanisms by which extracellular Aβ activates cytoplasmic NLRP3 inflammasome are poorly understood. Toll-like receptor 4(TLR4) acts as a sensor of Aβ and performs a key role in neuroinflammation. TLR4 is involved in activating the NLRP3 inﬂammasome in several diseases. In this study, the interaction between TLR4 and NLRP3 inflammasome in Aβ1−42 -induced neuroinflammation was investigated. BV-2 microglia and primary microglia were primed with lipopolysaccharide (LPS) and then pretreated with TLR4 inhibitor CLI-095, followed by stimulation with Aβ1–42 . The protein expression of NLRP3, the adaptor protein apoptosis-associated speck-like protein containing a CARD (ASC), and caspase-1 p 10 was detected by western blotting and immunostaining. The mRNA expression of inflammatory factors was measured by real-time PCR. The protein level of pro IL-1β and IL-1β was examined by ELISA. Activated microglia were examined by immunoﬂuorescence staining for ionized calcium-binding adapter molecule-1 (Iba-1). Conditioned medium of BV-2 cells was collected to challenge HT-22 neurons. Cell viability was assessed with MTT assay. Assessment of HT-22 cell apoptosis was performed by Annexin V/PI staining and western blotting to detect the protein level of cleaved caspase 3. The results showed that Aβ1−42 activated and up-regulated the expression of NLRP3 inflammasome in BV-2 microglia, as indicated by increased activation of caspase-1 and secretion of IL-1β. Pharmacological inhibition of TLR4 by CLI-095 abolished Aβ1−42 -induced NLRP3 inflammasome activation, which curbed the development of inflammation and exerted protective effect on HT-22 neurons. Furthermore, the inhibitory effects of CLI-095 on Aβ1−42 -induced inflammation were reversed by NLRP3 activator ATP. Overall, our findings suggested TLR4 mediated Aβ1−42 -induced NLRP3 inflammasome activation in mouse microglia. TLR4/NLRP3 pathway plays a critical role in Aβ1−42 -induced neuroinflammation.